2009
DOI: 10.1007/s11240-009-9543-9
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration and plantlet development from somatic tissues of Aristolochia fimbriata

Abstract: Aristolochia fimbriata is a small herbaceous perennial in the basal angiosperm family Aristolochiaceae. The family contains diverse floral forms ranging from radial to monosymmetric flowers with a wide variety of insect pollinators. Additionally, Aristolochia species contain secondary metabolites that are important natural toxins and traditional medicines, and are critical to the reproduction of swallowtail butterflies. These characteristics, in combination with the small genome size and short life cycle of A.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…During the present investigation, it has been clearly indicated that the highest root induction from shoot was obtained on IBA. These results are comparable with those described by other researchers for IBA induced rooting in other species (Bliss et al, 2009;Cheruvathur and Thomas, 2014b;Phulwaria et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…During the present investigation, it has been clearly indicated that the highest root induction from shoot was obtained on IBA. These results are comparable with those described by other researchers for IBA induced rooting in other species (Bliss et al, 2009;Cheruvathur and Thomas, 2014b;Phulwaria et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore alternative cytokinins may need to be considered for our chrysanthemum cultivars that were difficult to regenerate. The effect of explant source on direct shoot organogenesis has been reported by others (Pereira et al 2000;Dhar and Joshi 2005;Sharma and Nautiyal 2009;Bliss Plant Cell Tiss Organ Cult (2011) 107:295-304 301 et al 2009). Such variations can be attributed to age (Palmer and Keller 2011) and physiological condition of the explant, and are likely to be determined by genetic factors (Baroncelli et al 1978;Nagarathna et al 1991).…”
Section: Discussionmentioning
confidence: 56%
“…We have begun to develop inbred lines to facilitate genome mapping and large scale mutagenesis experiments. High-efficiency transformation with a GFP construct allows rapid, nondestructive identification of transformed tissues for subsequent processing, and our in vitro micropropagation and regeneration methods can yield greenhouse acclimated plants in three months [47]. Individual A. fimbriata plants survive indefinitely, providing ongoing access to mutant lines that can be cloned for distribution to the research community.…”
Section: Discussionmentioning
confidence: 99%
“…A protocol for genetic transformation of A. fimbriata was developed based on in vitro shoot regeneration [47] from leaf and stem explants coupled with Agrobacterium -mediated transformation. Leaf and internodal stem segments (2-3 cm long) from rooted tissue cultured A. fimbriata plants were excised and immediately immersed in induction media [46] to keep moist.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation